Perinatal Changes of Cardiac Troponin-I in Normal and Intrauterine Growth-Restricted Pregnancies - Nicoletta Iacovidou; Maria Boutsikou; Demetrios Gourgiotis; Despina D. Briana; Stavroula Baka; Venetia-Maria Vraila; Louiza Kontara; Demetrios Hassiakos; Ariadne Malamitsi-Puchner (Hindawi Limited, 2007)
Intrauterine growth restriction (IUGR) implies fetal hypoxia, resulting in blood flow redistribution and sparing of vital organs (brain, heart). Serum cardiac Troponin-I (cTnI), a well-established marker of myocardial ischaemia, was measured in 40 mothers prior to delivery, the doubly clamped umbilical cords (representing fetal state), and their 20 IUGR and 20 appropriate-for-gestational-age (AGA) neonates on day 1 and 4 postpartum. At all time points, no differences in cTnI levels were observed between the AGA and IUGR groups. Strong positive correlations were documented between maternal and fetal/neonatal values (r≥.498, P≤.025 in all cases in the AGA and r≥.615, P≤.009 in all cases in the IUGR group). These results may indicate (a) normal heart function, due to heart sparing, in the IUGR group (b) potential crossing of the placental barrier by cTnI in both groups